PENILAIAN KESIAPAN PUSTAKAWAN DALAM PENGEMBANGAN SMART LIBRARY: STUDI KASUS : PUSTAKAWAN DI LINGKUNGAN KEMENTERIAN PERTANIAN RI - Junaidi, Herwan; Henriyadi; Syaikhu HS, Akhmad (Perpustakaan Nasional RI, 2024)
Disruption changed all aspects of human beings, with no exception for the library. The library must be transformed traditional library into a smart library so that it is not abandoned by its users. A smart library is a “human-based library” that consists of four core components, namely smart services, smart people, smart place, and smart governance. Librarians have a prominent role in the implementation of the smart library. Libraries at the Ministry of Agriculture have the plan to transform their libraries into a smart libraries. Therefore, an assessment of the readiness of librarians within the Ministry of Agriculture is needed to ensure that transforming the library in the Ministry of Agriculture of Indonesia through developing smart libraries can run well. The result of the assessment indicates that in term of the number of librarians is quite enough. However, some training or capacity building is required in library management and information technology.